Moral Schemata in L2 Politeness: Sasak and Balinese EFL Learners’ Pragmatic Transfer - Wahyudiantari, Ni Wayan Prami; Rahman, Arif (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
Research in interlanguage pragmatics (ILP) has increasingly recognized that politeness is shaped not only by linguistic knowledge but also by the cultural values learners bring to interaction. However, evidence from Southeast Asian contexts remains limited, restricting current understanding of how local value systems influence pragmatic transfer. This study investigates how Indonesian EFL learners from two ethnolinguistic groups, Sasak (n = 30) and Balinese (n = 30), realize politeness in apology and refusal speech acts and how first-language (L1) moral schemata influence their pragmatic choices. Adopting a convergent mixed-methods design, the study combines discourse completion tasks (DCTs) with semi-structured interviews to examine both pragmatic performance and learners’ underlying reasoning. The findings reveal clear differences between the two groups. Sasak learners showed a stronger tendency toward negative politeness strategies, reflecting the value of humility (andap asor), whereas Balinese learners more frequently employed indirect strategies associated with maintaining social harmony (rwa bhineda). These differences suggest that pragmatic transfer is influenced not only by language proficiency but also by culturally shaped understandings of appropriate social conduct. The results further indicate that learners draw on locally shared value systems when managing face and interpersonal relationships in English. The study contributes to ILP scholarship by providing evidence that politeness is closely linked to culturally informed moral reasoning and by extending discussions of facework beyond dominant Western and East Asian perspectives. It also highlights the importance of incorporating intercultural and values-based dimensions into pragmatics instruction, enabling learners to develop greater awareness of how different communities interpret and enact politeness in communication.